Instagram communication strategies of European museums. - Rodríguez Vera, Ainhoa del Pino; De-las-Heras-Pedrosa, Carlos; Jambrino-Maldonado, Carmen (Taylor & Francis, 2024)
In recent years, new technologies have made it possible to reproduce cultural content through new social media tools, thus ensuring the development of cultural heritage on a global scale, but museums have not always seen the introduction of these media in their strategies in a positive way. This article focuses on the analysis of public engagement with the collections of the five most reputable museums in Europe through the visual social media platform, Instagram. The study explores public engagement through a mixed-methods approach, with data mining using the Fan Page Karma monitoring tool. The findings show the value of active listening and interaction with user-generated content as a key component of reputation and image, reflecting the importance of two-way communication. The research may also be useful in the future to help improve strategies in the digital ecosystems of museum institutions.
Keywords: Museos - Relaciones públicas; Redes sociales en Internet; Marketing en internet; COVID-19 - Influencia y consecuencias; Museum; Social media; Instagram; Communication strategy; Cultural tourism